MORPHOLOGICAL SIGNS OF THE HEPATIC FUNCTION DECOMPENSATION WITH EXPERIMENTAL COMPLETE OBSTRUCTION OF THE EXTRAHEPATIC BILE DUCTS - Mamontov I.М.; Ivakhno, I.V.; Tamm, T.I.; Panasenko, V.O.; Padalko, V.I.; Zulfugarov, I. (World of Medicine and Biology, 2019)
The complete obstruction of the extrahepatic bile ducts (COEHBD) in the experiment is accompanied by changes in the liver, which can display its function decompensation, which causes the death of animals. The purpose of the project was to study the liver morphological changes in experimental COEHBD, depending on the obstruction duration and the mortality associated with it. The simulation of COEHBD was performed on 36 rats by ligation and transection of the choledoch. Animals were sacrificed on the 3rd, 7th, 14th, 21st, 28th and 35th days. Histological and morphometric liver studies were carried out. Pathological changes in the liver were progressive at the peak of lethality (7 out of 11 dead animals) within the last two weeks of the experiment and were characterized by: proliferation of the bile ducts, proliferation and hyperplasia of hepatocytes, the growing number of sinusoidal cells, fibrosis with a complete loss of the normal liver histoarchitectonics and replacing of its parenchyma with proliferating. bile ducts. The morphological signs preceding the liver function decompensation, which is accompanied by the mortality peak with COEHBD, are: the maximum value of the portal zones density index and the sinusoid- hepatocytes number, the nuclear-cytoplasmic hepatocytes ratio reduction after the previous maximum, which accordingly reflects the maximum proliferative activity of the bile ducts and the activity of sinusoidal cells against the background of the hepatocytes proliferative capacity reduction.